Successful discontinuation of eculizumab under immunosuppressive therapy in DEAP-HUS - Hackl, Agnes; Kirschfink, Michael; Beck, Bodo Bernhard; Weber, Lutz T.; Habbig, Sandra (Pediatric nephrology, 2017)
Background: Deficiency of complement factor H-related plasma proteins and complement factor H autoantibody-positive hemolytic uremic syndrome (DEAP-HUS), which is characterized by the deficiency of complement-factor H-related (CFHR) plasma proteins and the subsequent formation of autoantibodies against complement factor H (CFH), has been reported to have an adverse outcome in one third of patients. Therapy options include prompt removal of antibodies by plasma exchange and immunosuppressive therapy. Recently, restoration of complement control using the monoclonal antibody eculizumab has been shown to be effective as first- and as second-line therapy in cases of therapy resistance or severe side effects of the applied therapy.Diagnosis/treatmentHere, we report a 6-year-old girl with DEAP-HUS and first-line therapy with eculizumab under immunosuppressive therapy with glucocorticoids and mycophenolate mofetil (MMF). This therapy led to a prompt and sustained clinical recovery, to a stable reduction of complement activation, and to a rapid decline in autoantibody titer. A second increase in the autoantibody titer was successfully treated with methylprednisolone and the child remained in remission. After 8.3 months of sustained complement control and 4.5 months of stable antibody suppression, eculizumab was successfully discontinued without any sign of relapse.ConclusionsTo our knowledge, this is the first reported case of a child with DEAP-HUS treated with the combination of eculizumab and immunosuppression as first-line therapy avoiding any HUS- or therapy-related complications and resulting in prompt clinical recovery. Importantly, clinical remission is maintained after discontinuation of eculizumab under stable immunosuppression.